2008
DOI: 10.1016/j.jim.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel chemokine-mediated in vivo T cell recruitment assay

Abstract: Trafficking of leukocytes to sites of inflammation is an important step in the establishment of an immune response. Chemokines are critical regulators of leukocyte trafficking and are widely studied molecules for their important role in disease and for their potential as new therapeutic targets. The ability of chemokines to induce leukocyte recruitment has been mainly measured by in vitro chemotaxis assays, which lack many components of the complex biological process of leukocyte migration and therefore provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…However, the CXCL11 gene in C57BL/6 mouse strain, from which NSG mouse was developed, contains a point mutation and a single-base deletion that results in a reading frame shift. Hence, a non-functional CXCL11 protein product is produced [24]; only CXCL9 and CXCL10 are probably the functional chemokines in this cluster to act on and to attract OT-I cell migration to the treated tumors. The data also revealed significant elevation of several additional chemokines.…”
Section: Resultsmentioning
confidence: 99%
“…However, the CXCL11 gene in C57BL/6 mouse strain, from which NSG mouse was developed, contains a point mutation and a single-base deletion that results in a reading frame shift. Hence, a non-functional CXCL11 protein product is produced [24]; only CXCL9 and CXCL10 are probably the functional chemokines in this cluster to act on and to attract OT-I cell migration to the treated tumors. The data also revealed significant elevation of several additional chemokines.…”
Section: Resultsmentioning
confidence: 99%
“…Chemokines and chemokine receptors guide the migration of effector cells into inflammatory sites, which are critical for the pathogenesis of autoimmune diseases [3, 4, 33, 34]. However, the observation in TGC3 mice that inflammatory cells accumulate within the inflammatory sites of liver in the absence of CXCR3 suggests that the pathogenic role of CXCR3 deficient CD8+ T cells does not require the chemotaxis of CXCR3 and is likely mediated either by other redundant chemokine(s) mediated chemotaxis or due to the absence of inhibitory signals normally provided by CXCR3 ligation.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR3 is upregulated following CTL and Th1 cell differentiation [2]. CXCL9 (MIG), CXCL10 (IP-10), and CXCL11 are the natural ligands of CXCR3 [35]. CXCR3 is functionally pleiotropic; it plays an important role in the chemotaxis of Tregs to sites of inflammation following binding [6, 7], but also participates in T cell differentiation [5, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts by us have shown that a direct intratracheal administration of mouse IP-10 into the lungs of C57BL/6 mice dose-responsively recruited exogenously and systemically administered ex vivo activated syngeneic OT-1 CD8þ T cells 48 h before the IP-10 challenge and that 5.0 mg of intratracheal IP-10 gave an good signal-to-noise-ratio [41]. Figure 3 shows that this IP-10 induced in vivo cell migration can be significantly and dose-responsively mitigated by systemic injection of the 20A9 mAb.…”
Section: Mab Clone 20a9 Antagonizes Ip-10 Induced Cell Migration In Vivomentioning
confidence: 98%